2018
DOI: 10.1016/j.yjmcc.2018.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutrophils in CVB3 infection and viral myocarditis

Abstract: Coxsackievirus B3 (CVB3) is a globally prevalent enterovirus of the Picornaviridae family that is frequently associated with viral myocarditis (VM). Neutrophils, as first responders, may be key cells in determining viral disease outcomes; however, neutrophils have been poorly studied with respect to viral infection. Although neutrophils have been ascribed a relevant role in early cardiac inflammation, their precise role in CVB3 infection has not yet been evaluated. In this study, we aimed to determine if the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…For instance, IL-6 inhibits the anticancer response by dampening the IL27/STAT1 signalling pathway [51]. IL-8 is mainly responsible for the recruitment of neutrophils, basophils and T cells [52, 53]. Moreover, accumulated evidence has revealed that IL-8 promotes angiogenesis and metastasis in tumour cells [54].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IL-6 inhibits the anticancer response by dampening the IL27/STAT1 signalling pathway [51]. IL-8 is mainly responsible for the recruitment of neutrophils, basophils and T cells [52, 53]. Moreover, accumulated evidence has revealed that IL-8 promotes angiogenesis and metastasis in tumour cells [54].…”
Section: Discussionmentioning
confidence: 99%
“…Our group reported a robust accumulation of neutrophils in the infected hearts of CVB3-infected mice which peaked 3 dpi. However, mAbs depletion of peripheral neutrophils had no effect on viral titer and the heart pathology (44), whereas it is reported that neutrophils internalized CVB3 and increased viral dissemination as well as viral myocarditis (45). However, Althof et al (46) found that injection of mice with ONX 0914, a preclinical immunoproteasome-specific inhibitor to treat CVB3 myocarditis, induced neutrophilia in blood.…”
Section: Discussionmentioning
confidence: 99%
“…This mobilization occurs earlier than that of any other infiltrated innate immune cells. Depletion of neutrophils in CVB3-infected mice results in reduced myocarditis 92 . Neutrophils can maintain inflammation by a specific process called NETosis, which involves the formation of neutrophil extracellular traps.…”
Section: Mast Cells Natural Killer Cells and Dendritic Cellsmentioning
confidence: 99%